On the ocean : the Mediterranean and the Atlantic from prehistory to AD 1500 - Cunliffe, Barry W. (Oxford University Press, 2017)
The story of the contest between humans and the sea, played out in the Mediterranean and the Atlantic from early prehistory until AD 1500.